Vertical industry relations, spillovers and productivity: evidence from Chilean plants - Ricardo A. López; Jens Suedekum (Institute for the Study of Labor (IZA), 2007)
We use disaggregated data on Chilean plants, and the Chilean input-output table to examine the impact of agglomeration spillovers on total factor productivity (TFP). In common with previous studies, we find evidence of intra-industry spillovers, but no evidence of cross-industry spillovers in general. This picture changes, however, when we take vertical industry relations into account. We find important productivity spillover effects from plants in upstream industries. Interestingly, a similar effect cannot be found from plants in downstream industries. The number of plants in these sectors has no effect on firm level TFP, just as the number of plants in other industries that are neither important upstream suppliers nor downstream customers also has no effect. Agglomeration effects are stronger for small than for large plants.
Keywords: 330; Vertical linkages; agglomeration; productivity; Chile; Agglomerationseffekt; Interindustrielle Verflechtung; Produktivität; Verarbeitendes Gewerbe; Lieferanten-Kunden-Beziehung; Input-Output; Chile